THE ACTIVITIES OF ZHANYBEK KAZY IN THE BASMACHI MOVEMENT (Based on archival materials) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article in official materials presents the life, work, followers, religious figure, tribal leader Zhanybek Kazy Sagynbayev. He opposed the Soviet power, was one of the organizers of the Basmachi movement. The Basmachi movement in Uzgen was headed by Kazy Zhanybek and other former commanders who conducted nationalist propaganda. They noted the mistakes in the division of the peoples of Central Asia into state entities based on nationality, carried out in 1924. The reason for their resistance to the division of state structures based on nationality was that they called on those who professed Islam to become one nation. It is also reported that Zhanybek Kazy had connections with anti-Soviet circles in Central Asia and leaders of the anti-Soviet policy movement abroad. It is also proven that Zhanybek Kazy emigrated abroad for self-defense. During the study of archival data, it was proven that these people reflected the struggle for independence in the territory of modern Alay-Gulchinsky, Sovietsky and Uzgensky districts. The study emphasizes that Zhanybek Kazy, as an outstanding personality of his time, occupies a worthy place on the pages of Kyrgyz history.
Keywords: Basmach , korbashi, Kazy, Muslim, Soviet power